Exploring levels of egg parasitism and variation in egg cuticular chemistry in different Clavigralla spp. (16th May 2019) - Kpongbe, Hilaire; Van den Berg, Johnnie; Khamis, Fathiya; Tamò, Manuele; Talamas, Elijah Jacob; Torto, Baldwyn
Abstract: Clavigralla spp. (Hemiptera: Coreidae) are major pests of cowpea ( Vigna unguiculata (L.) Walp, Fabacae), common bean ( Phaseolus vulgaris L., Fabacae) and pigeon pea ( Cajanus cajan L., Fabacae) in Africa. Clavigralla spp. egg parasitoids, Gryon spp. (Hymenoptera: Scelionidae), have previously been reported as potential biological control candidates. Little is known about the parasitism levels and their potential relationship with cuticular chemistry of Clavigralla spp. The aims of this study were to determine parasitism levels of Clavigralla tomentosicollis Stål (Hemiptera: Coreidae) and C. elongata Signoret (Hemiptera: Coreidae) eggs, and to explore the relationship between egg parasitism and egg cuticular chemistry. High parasitism levels were determined for C. tomentosicollis by collecting eggs from plants in mono‐cropping and multi‐cropping systems in farmers' fields in Bénin and Kenya between April and June 2016. Three species of Clavigralla were recorded: C. tomentosicollis, C. shadabi and C. elongata . Clavigralla tomentosicollis was the most common in both countries, while C. shadabi and C. elongata were only collected in Bénin and Kenya, respectively. An egg parasitoid ( Gryon sp.) was recovered from egg batches collected from both countries. In parasitism assays using Gryon sp., the incidence of parasitism was higher in C. tomentosicollis eggs than that of C. elongata . Chemical analysis by coupled gas chromatography/mass spectrometry (GC/MS) of cuticular extracts obtained from C. tomentosicollis and C. elongata eggs identified fifteen compounds including ten alkanes of which the amounts varied between the two species. We speculate that Clavigralla spp. cuticular chemistry may serve as potential host location cues for Gryon sp.